High‐density lipoprotein inhibits human M1 macrophage polarization through redistribution of caveolin‐1. (30th October 2015) - Lee, Man K S; Moore, Xiao‐Lei; Fu, Yi; Al‐Sharea, Annas; Dragoljevic, Dragana; Fernandez‐Rojo, Manuel A; Parton, Robert; Sviridov, Dmitri; Murphy, Andrew J; Chin‐Dusting, Jaye P F
Abstract : Background and Purpose: Monocyte‐derived macrophages are critical in the development of atherosclerosis and can adopt a wide range of functional phenotypes depending on their surrounding milieu. High‐density lipoproteins (HDLs) have many cardio‐protective properties including potent anti‐inflammatory effects. We investigated the effects of HDL on human macrophage phenotype and the mechanisms by which these occur. Experimental Approach: Human blood monocytes were differentiated into macrophages in the presence or absence of HDL and were then induced to either an inflammatory macrophage (M1) or anti‐inflammatory macrophage (M2) phenotype using LPS and IFN‐γ or IL‐4, respectively. Key Results: HDL inhibited the induction of macrophages to an M1‐phenotype, as evidenced by a decrease in the expression of M1‐specific cell surface markers CD192 and CD64, as well as M1‐associated inflammatory genes TNF‐α, IL‐6 and MCP‐1 (CCL2). HDL also inhibited M1 function by reducing the production of ROS. In contrast, HDL had no effect on macrophage induction to the M2‐phenotype. Similarly, methyl‐β‐cyclodextrin, a non‐specific cholesterol acceptor also suppressed the induction of M1 suggesting that cholesterol efflux is important in this process. Furthermore, HDL decreased membrane caveolin‐1 in M1 macrophages. We confirmed that caveolin‐1 is required for HDL to inhibit M1 induction as bone marrow‐derived macrophages from caveolin‐1 knockout mice continued to polarize into M1‐phenotype despite the presence of HDL. Moreover, HDL decreased ERK1/2 and STAT3 phosphorylation in M1 macrophages. Conclusions and Implications: We concluded that HDL reduces the induction of macrophages to the inflammatory M1‐phenotype via redistribution of caveolin‐1, preventing the activation of ERK1/2 and STAT3. Linked Articles: This article is part of a themed section on Inflammation: maladies, models, mechanisms and molecules. To view the other articles in this section visithttp://dx.doi.org/10.1111/bph.2016.173.issue-4